Phylogenetic Relationship of Barnacles (Fam:Balanidae) Sampled on Artificial Substrata of Kuala Selangor and Morib - N Roseman, N; Rasol, R; Ismail, A; R Singh, H; Z M Yusof, F (International Journal of Engineering and Technology, 2019)
Barnacles are marine sessile crustacean inhabiting intertidal areas of the Selangor coastline. They are seen attaching themselves to rocks and artificial structures such as jetty, piers, boats and sea walls. Being the most successful biofoulers, barnacles cause economic losses to some extent. Most of barnacles study focused on morphological identification only. Since molecular method gave more accurate results by sequence comparison, species identification was done on samples of obviously different species inhabiting artificial substrata by using mitochondrial 16S rDNA identification. In Kuala Selangor, there was only one species found on artificial substrata in Bagan Pasir and Pasir Penambang which was identified as Amphibalanus cirratus. Two species that differed in their morphological characteristics found on Morib sea walls were identified as Amphibalanus cirratus and Chthamalus malayensis. Phylogenetic tree based on the 16S rDNA showed that all the samples were in the same cluster reflecting that they are in the same clade.Â Â